Initiatives by Subsidiaries of Multinational Corporations An Empirical Study on the Influence of Subsidiary Role Context - Dzedek, Lars R. (Springer Fachmedien Wiesbaden : Gabler, 2018)
In the field of international business, it is increasingly recognized that Multinational Corporations (MNCs) can no longer rely on headquarters as the single source of competitive advantage. Therefore, growing interest centers on decentralized entrepreneurial initiatives that originate in their network of foreign subsidiaries. Based on an extensive review of literature, Lars R. Dzedek develops a comprehensive framework to help explain how the setting in which a foreign subsidiary operates impacts its entrepreneurial initiatives and outcomes. The author conducts an empirical investigation in 14 foreign units of two large MNCs and offers detailed case studies with rich insights into entrepreneurial subsidiary activities. Contents Critical Review of the Literature on Subsidiary Initiatives Framework for Role-Specific Subsidiary Initiative-Taking Empirical Study and Findings from Two Multinational Corporations Implications for International Business Research and Management Practice Target Groups Researchers and students in the field of international management, entrepreneurship and innovation Managers in Multinational Corporations The Author Dr. Lars R. Dzedek finished his doctorate at ESCP Europe Wirtschaftshochschule Berlin, Chair of International Management and Strategic Management. He now leads the regional office of an internal management consulting firm of a large Multinational Corporation.